EKSPERIMENTASI MODEL PROBLEM BASED LEARNING (PBL) DAN MODEL GROUP INVESTIGATION (GI) DALAM PEMBELAJARAN MATEMATIKA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI SIKAP PERCAYA DIRI SISWA KELAS VIII SMP SE-KABUPATEN MADIUN TAHUN PELAJARAN 2013/2014 - Ubayu Wahyuning Awi Gangga; Tri Atmojo Kusmayadi; Budi Usodo (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research was arranged to determine: (1) which one gave better achievement between PBL, GI or direct learning; (2) which one have better achievement between high, medium or low self confidence students; (3) for each self confidence categories, which one gave better achievement between PBL, GI or direct learning; (4) for each learning model, which one have better achievement between high, medium or low self confidence students. The type of the research was a quasi-experimental research. The population was the students of junior high school in Madiun regency on academic year 2013/2014. The size of the sample was 235 students consisted of 77 students in the first experimental group, 79 students in the second experimental group and 79 students in the control group. The instruments used were documentation, questionnaire, and mathematics achievement test. The data was analyzed using unbalanced two way analysis of variance. The conclusions of the research were as follows. (1) The model of GI learning gave better achievement in studying mathematics than PBL and direct learning, PBL gave better achievement in studying mathematics than direct learning; (2) The students who have high self confidence have a better achievement than the students who have medium and low self confidence, but the students who have medium self confidence have the same achievement as the students who have low self confidence; (3) On the students with high self confidence, the PBL and GI gave the same achievement, but PBL and GI gave better achievement than direct learning, while on the students with medium and low self confidence, the PBL, GI and direct learning gave the same achievement; (4) On the PBL, high self confidence students have better achievement than low self confidence students, but have the same achievement as medium self confidence students, and medium self confidence students have the same achievement as low self confidence students. While on GI and direct learning, the three categories of self confidence students have the same achievement.Keywords: Problem Based Learning (PBL), Group Investigation (GI), Direct Learning, Self Confidence.